2019
DOI: 10.3389/fmicb.2019.01038
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mathematical Model for Studying Antimicrobial Interactions Against Campylobacter jejuni

Abstract: The aim of this study is to investigate the antimicrobial synergistic effect against Campylobacter jejuni , a leading foodborne pathogen that causes human gastroenteritis, by cinnamon oil, encapsulated curcumin, and zinc oxide nanoparticles (ZnO NPs). We compared three approaches to study the antimicrobial interactions, including the time-killing method, the fractional inhibitory concentration index (FICI) method, and a mathematical concentration-effect model. Isobologram analysis was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…The 96-well microtiter plate was incubated in an orbital shaker under microaerobic conditions at 37°C for 48 h. After incubation, the optical density was determined using a 96-well plate reader (BioTek Instruments Inc., Winooski, VT) at 595 nm (OD 595 ). The concentrations and absorbance values were graphed on a logarithmic plot using GraphPad Prism (v6.0.h, La Jolla, CA), and the IC 50 was calculated from the concentration-effect curve as described previously ( Hakeem et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The 96-well microtiter plate was incubated in an orbital shaker under microaerobic conditions at 37°C for 48 h. After incubation, the optical density was determined using a 96-well plate reader (BioTek Instruments Inc., Winooski, VT) at 595 nm (OD 595 ). The concentrations and absorbance values were graphed on a logarithmic plot using GraphPad Prism (v6.0.h, La Jolla, CA), and the IC 50 was calculated from the concentration-effect curve as described previously ( Hakeem et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, the evaluation of synergism requires accurate methods to study drug interaction, considering potential differences between the dose-response relationship of individual drugs and avoiding over-or under-estimation of interactionS. For example, while the time-kill curve of C. jejuni treated with both cinnamon oil and ZnO NPs resulted in the over-estimation of synergism between the antimicrobials, the fractional inhibitory concentration index (FICI) method showed no synergism but only an additive effect [233]. The FICI method was not able to detect the synergism between binary combinations of antimicrobials (cinnamon oil, ZnO NPs, and CUR encapsulated in starch) at sub-MIC, which resulted in the non-turbidity of C. jejuni.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In turn, mathematical modeling using isobolograms and median-effect curves showed synergism when CUR in starch was combined with other antimicrobials against C. jejuni, with bacterial reductions of 3 log for the binary combination and over 8 log for the tertiary combination. The mathematical modeling suggested that CUR in starch was the main antimicrobial responsible for the synergistic interaction [233].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The method was based on previous experiments with some modifications ( Xiao et al, 2015 ; Hakeem et al, 2019 ). The time-killing curve test was conducted to verify the time it took to kill all the bacteria.…”
Section: Green-route Synthesis Of Agnpsmentioning
confidence: 99%